Development Problems of Information Provision on the Management of High Technology Park - Aliyev, Alovsat Garaja; Shahverdiyeva, Roza Ordukhan (Journal of Information, 2017)
The paper investigates transition to innovation-based information economy in Azerbaijan. The features of new economy are analyzed and the roles of high technology parks are shown. The main objectives, functions and features of the establishment of high technology parks, as well as organization of the activity of the structural elements, which are the parking complex and their interactions are analyzed. The development of comprehensive management system at high technology parks is studied. In addition, the methods are proposed for the development of information systems supporting decision making in systematic and sustainable management of the parks. Various blocks, functions and structural elements included in the information provision systems of high technology parks are analyzed.